The Development of the Idea of Freedom in the Literary-Philosophical Works of Sartre - Mayilyan, Alvard (History and Culture, 2025)
The article analyzes the changes and expressions of the classical definition of the chronotope in the novel-screenplay by Jean-Paul Sartre " The Chips are Down", as well as new manifestations of the space-time concept through the depiction of memories and the afterlife of the characters.New manifestations of the chronotope are explored through the memories and imagination of the characters, as well as the technique of the double chronotope, the introduction of fantastic elements into the text as an interpretation of the author's philosophical views.
Keywords: existentialism; memory; freedom; responsibility; society; being